1981
DOI: 10.1002/j.1552-4604.1981.tb02573.x
|View full text |Cite
|
Sign up to set email alerts
|

Levonantradol for Chemotherapy‐Induced Emesis: Phase I—II Oral Administration

Abstract: Thirty five patients were enrolled into a Phase I‐II study of oral levonantradol being tested as an antiemetic for chemotherapy patients who were refractory to the aggressive use of standard antiemetic agents. Sixty‐nine total courses were given. Dysphoric reactions (fear, anxiety, hallucinations) were the most serious side effects, and were most prevalent at the highest dose tested (2.0 mg q4h). Somnolence, a “high” feeling, hypotension were also noted. Antiemetic responses were seen at 0.5, 1.0, 1.5 and 2.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 9 publications
1
10
0
1
Order By: Relevance
“…Altogether, these studies have M a n u s c r i p t 10 revealed a dose-dependent switch from reward to aversion, with low and high doses of cannabinoids inducing reward and aversion, respectively. An analogous phenomenon has been observed in human addicts, where low doses of THC or levonantradol are perceived as rewarding while higher doses as aversive (Noyes et al, 1975, Raft et al, 1977Laszlo et al, 1981).…”
supporting
confidence: 58%
“…Altogether, these studies have M a n u s c r i p t 10 revealed a dose-dependent switch from reward to aversion, with low and high doses of cannabinoids inducing reward and aversion, respectively. An analogous phenomenon has been observed in human addicts, where low doses of THC or levonantradol are perceived as rewarding while higher doses as aversive (Noyes et al, 1975, Raft et al, 1977Laszlo et al, 1981).…”
supporting
confidence: 58%
“…It is well known that, with high doses, ∆ 9 -THC can cause dysphoria and even panic in human subjects (Raft et al 1977;Laszlo et al 1981). In laboratory animals, cannabinoids also possess an anxiogenic profile and stimulate the hypothalamo-pituitary axis in a manner similar to foot shock with a concomitant c-fos expression in stress-related loci (central and basolateral nuclei of the amygdala and periaqueductal grey in particular; Herkenham and Brady 1994).…”
Section: Discussionmentioning
confidence: 97%
“…This clinical application was thwarted as a result of the untoward side effects of memory impairment, cognitive dysfunction, and sedation [4,5], but has recently been reconsidered [6]. Although pharmaceutical development included treatment of nausea in cancer chemotherapy [7], the only CB 1 agonists to succeed to market have been dronabinol (also known as • 9 -tetrahydrocannabinol (THC)) and nabilone [810]. …”
Section: Cb1 Cannabinoid Receptor Physiology Pathology and Pharmacologymentioning
confidence: 99%